A comprehensive protocol to test instrumented treadmills. Issue 6 (June 2015) - Sloot, L.H.; Houdijk, H.; Harlaar, J.
Highlights: A protocol to assess sources of systematic errors for instrumented treadmills. With accuracy, linearity, crosstalk, speed change, resonance, drift, warming, noise. The performance of 2 treadmills is measured following the protocol. The protocol provides guidelines for reporting and technical quality assurance. Abstract: Instrumented treadmills are becoming more common in gait analysis. Due to their large and compliant structure, errors in force measurements are expected to be higher compared with conventional force plates. There is, however, no consistency in the literature on testing the performance of these treadmills. Therefore, we propose a standard protocol to assess and report error sources in instrumented treadmills. The first part of this protocol consists of assessment of the accuracy of forces and center of pressure (COP), including non-linearity, hysteresis and crosstalk. The second part consists of (novel) instrumented resonance testing and belt speed variability tests. The third part focuses on measurement variability over time, including drift, warming of the system and noise. The performance of two in-house instrumented treadmills with different dynamics was measured. Differences were found between the treadmills in COP accuracy (4.0 mm versus 6.5 mm), lowest eigen frequency (35 Hz versus 23 Hz) and noise level at 5 km/h (10 N versus 29 N). The loaded treadmills both showed a 3.3% belt speed variability at 5 km/h. Thus, the protocol was able to characterize strong and weak characteristics of the treadmills and allowed for a proper judgement on the validity of the instruments and their application in the domain of gait analysis. We propose to use this protocol when testing and reporting the performance of instrumented treadmills.